1952
DOI: 10.1590/s0006-87051952000200004
|View full text |Cite
|
Sign up to set email alerts
|

Observações citológicas em Coffea: XIX - Microsporogênese em Coffea dewevrei

Abstract: Coffea Dewevrei De Wild, et Th. Dur. is a diploid species with 2n = 22 chromosomes. Details on the microsporogenesis are presented in this paper. From pachynema to diakynesis the 11 bivalents were well differentiated into achromatic and chromatic regions : the centromere was in all chromosomes surrounded by deeply chromatic zones. Only one pair of chromosomes was found to be attached to the nucleolus; it has a submedian centromere, the organizing region seeming to be located in the sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These studies indicated a uniform number of chromosomes (2n=44) for all varieties of C. arabica, and it was demonstrated for the first time that, despite the tetraploid condition, this species shows normal meiotic behavior. Subsequently, many other species, varieties, cultivars, and interspecific hybrids, with different levels of ploidy, such as triploids, tetraploids, hexaploids and octoploids, also had their chromosome number established (Krug, 1937, Mendes, 1938Medina, 1950Medina, , 1952Medina, , 1972.…”
Section: Number and Morphology Of Coffee Chromosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicated a uniform number of chromosomes (2n=44) for all varieties of C. arabica, and it was demonstrated for the first time that, despite the tetraploid condition, this species shows normal meiotic behavior. Subsequently, many other species, varieties, cultivars, and interspecific hybrids, with different levels of ploidy, such as triploids, tetraploids, hexaploids and octoploids, also had their chromosome number established (Krug, 1937, Mendes, 1938Medina, 1950Medina, , 1952Medina, , 1972.…”
Section: Number and Morphology Of Coffee Chromosomesmentioning
confidence: 99%
“…rugosa to explain the low productivity of this variety and the lack of the wrinkled (rugosa) characteristic in the progenies of these plants. In addition to these varieties of C. arabica, similar analyses on microsporogenesis were made for several diploid species of Coffea, mainly those used in interspecific hybridizations with C. arabica Medina, 1952;Conagin, 1961;Medina and Rijo, 1969;Medina et al, 1977;Boaventura and Cruz, 1987). However, despite these studies on meiotic behavior, the characterization of individual chromosomes remained an important desideratum for progress with cytological research on coffee.…”
Section: Cytogenetics and Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrids between the species C. arabica and C. canephora have been obtained on different occasions, and they are called "Arabusta" (Mendes 1950). Because of its importance, meiotic behavior had already been studied to some F 1 hybrids and also to parental plants in order to explore the genetic resources of these hybrids (Mendes 1950;Medina 1952;Medina 1963;Mônaco and Medina 1965;Medina and Rijo 1969;Reddy and Narayan 1981;Owuor 1985;Boaventura and Cruz 1987;Boaventura 1990).…”
Section: Introductionmentioning
confidence: 99%